Variations in the Mitochondrial Genome of a Goldfish-Like Hybrid [Koi Carp (♀) × Blunt Snout Bream (♂)] Indicate Paternal Leakage - Wang, Yude; Sun, Wenzhen; Gu, Qianhong; Yao, Jiajun; Tan, Huifang; Huang, Xu; Qin, Qinbo; Tao, Min; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2021)
Previously, a homodiploid goldfish-like fish (2n=100; GF-like) was spontaneously generated by self-crossing a homodiploid red crucian carp-like fish (2n=100; RCC-like), which was in turn produced via the distant hybridization of female koi carp (Cyprinus carpio haematopterus, 2n=100) and male blunt snout bream (Megalobrama amblycephala, 2n=48). The phenotypes and genotypes of RCC-like and GF-like differed from those of the parental species, but were similar to wildtype diploid red crucian carp (2n=100; RCC) and goldfish (2n=100; GF), respectively. We sequenced the complete mtDNAs of the KOC, BSB, RCC-like, GF-like, and subsequent generations produced by self-crossing (RCC-L-F2–3 and GF-L-F2). Paternal mtDNA fragments were stably embedded in the mtDNAs of the both lineages, forming chimeric DNA fragments. In addition to these chimeras, several nucleotide positions in the RCC-like and GF-like lineages differed from the parental bases, and were instead identical with wildtype red crucian carp and goldfish, respectively. Moreover, RCC-like and GF-like mtDNA organization and nucleotide composition were more similar to those of RCC and GF, respectively, as compared to parental mtDNA. Finally, phylogenetic analyses indicated that RCC-like and GF-like clustered with wildtype red crucian carp and goldfish, not with the parental species. The molecular dating time show that the divergence time of KOC and GF was about 21.26 Mya [95% highest posterior density (HPD): 24.41-16.67 Mya], which fell within the period of recent. The heritable chimeric DNA fragments and mutant loci identified in the mtDNA of the RCC-like and GF-like lineages provided important evidence that hybridizations might lead to changes in the mtDNA and the subsequent generation of new lineages. Our findings also demonstrated for the first time that the paternal mtDNA were transmitted into the mtDNA of homodiploid lineages (RCC-like and GF-like), which provided evidence that paternal DNA plays a role in inherited mtDNA. These evolutionary analyses in mtDNA suggest that goldfish might have diverged from red crucian carp after red crucian carp diverged from koi carp.